(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The global economic situation and need to be better prepared for competitive challenges put pressure on modern companies to shift toward automation and digitalization. As a consequence of rapid technological development and the speed of change and therefore forced transformation of business models and work design, organizations are faced with a need for a massive change of features and an extended role of HR management processes. To be able to drive future organizational performance, HR leaders and professionals are required to make changes in the skills and competencies they have and to acquire and possess new ones. The critical components of a digital transformation strategy that can help achieve a competitive advantage are human capital, intellectual capital, and knowledge. The purpose of this paper is to explore and elaborate on the contemporary position and the changing function of HRM in light of digital transformation. In that sense, a comprehensive analysis of available literature has been conducted addressing the domains of HR planning, reward management, performance management, employee engagement, training and development, health and safety, employee relations, as well as their change under the influence of digital transformation. As the main conclusion of this research, it can be stated that although digitalization, i.e., digital transformation, strongly affects HR practices and procedures specifically by using human resources information systems, the role of HR in contributing to the digitization strategy is not sufficiently emphasized. However, it can be argued that the results of this research represent a valuable contribution to future research and can certainly be an important benchmark for organizations when preparing strategies to respond to the challenges of the digital age.